FLEXIBLE STRUCTURES ARE SUSCEPTIBLE TO EXTERNAL FORCED VIBRATION, SUCH AS VIBRATION EXERTED BY WIND LOADING. IN THIS PRESENT WORK, A HIGH-RISE BUILDING CONFIGURATION IS EVALUATED. A HIGH-RISE BUILDING CONFIGURATION TYPICALLY ALLOWS SOME FLEXIBILITY DURING FORCED EXCITATION. HOWEVER, VIBRATION ALSO MAY CAUSE DISCOMFORT FOR THE PEOPLE INSIDE THE BUILDING OR STRUCTURAL FAILURE IF THE VIBRATION IS LARGE ENOUGH. THUS, DAMPING IS ESSENTIAL TO CONTROL OR MINIMIZE THE DEFORMATION OF THE BUILDING. ONE OF THE MITIGATIONS THAT CAN BE DONE AND HAVE BEEN WIDELY APPLIED TO HIGH-RISE BUILDINGS IS TO USE A PASSIVE DAMPER SYSTEM SUCH AS A TUNED MASS DAMPER (TMD). THE RESEARCH IN THIS FINAL PROJECT IS FOCUSED ON ANALYZING THE IMPLEMENTATION OF A TMD SYSTEM IN REDUCING THE VIBRATIONS ON A HIGH-RISE BUILDING SUBJECTED TO WIND LOAD EXCITATION. THE BUILDING STRUCTURE AND TMD SYSTEM ARE MODELED EMPLOYING THE FINITE ELEMENT METHOD. BEAM ELEMENTS REPRESENT THE STRUCTURE, AND THE WIND LOAD IS APPLIED WITH DISTRIBUTED NODAL FORCES. VERIFICATION OF THE BUILDING MODEL IS CONDUCTED BY COMPARISON OF NATURAL DYNAMIC CHARACTERISTICS FOUND IN THE REFERENCE LITERATURE. BASED ON THE ANALYSIS RESULTS, THE TMD SYSTEM WAS FOUND TO BE QUITE EFFECTIVE IN REDUCING THE VIBRATIONS EXERTED BY THE WIND LOADING. IN THIS PARTICULAR STUDY, IT IS FOUND THAT THE VIBRATION RESPONSES CAN BE REDUCED BY UP TO 40%. KEYWORDS: FLEXIBLE STRUCTURES, HIGH-RISE BUILDING, WIND EXITED LOADING, TUNED MASS DAMPER, FINITE ELEMENT METHOD - Nurul Aini, Faujiah
Flexible structures are susceptible to external forced vibration, such as vibration exerted by wind loading. In this present work, a high-rise building configuration is evaluated. A high-rise building configuration typically allows some flexibility during forced excitation. However, vibration also may cause discomfort for the people inside the building or structural failure if the vibration is large enough. Thus, damping is essential to control or minimize the deformation of the building. One of the mitigations that can be done and have been widely applied to high-rise buildings is to use a passive damper system such as a tuned mass damper (TMD). The research in this final project is focused on analyzing the implementation of a TMD system in reducing the vibrations on a high-rise building subjected to wind load excitation. The building structure and TMD system are modeled employing the finite element method. Beam elements represent the structure, and the wind load is applied with distributed nodal forces. Verification of the building model is conducted by comparison of natural dynamic characteristics found in the reference literature. Based on the analysis results, the TMD system was found to be quite effective in reducing the vibrations exerted by the wind loading. In this particular study, it is found that the vibration responses can be reduced by up to 40%.